2012
DOI: 10.1103/physreve.85.036207
|View full text |Cite
|
Sign up to set email alerts
|

Intermingled basins in coupled Lorenz systems

Abstract: We consider a system of two identical linearly coupled Lorenz oscillators presenting synchronization of chaotic motion for a specified range of the coupling strength. We verify the existence of global synchronization and antisynchronization attractors with intermingled basins of attraction such that the basin of one attractor is riddled with holes belonging to the basin of the other attractor and vice versa. We investigated this phenomenon by verifying the fulfillment of the mathematical requirements for inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 40 publications
(74 reference statements)
0
26
0
Order By: Relevance
“…The mechanism for induced multistability in the case of global coupling can be understood in a similar manner. However, in addition to synchronized attractors appearing due to the fixed points A ∓ , the systems can also exhibit other attractors, A 1,2 , similar to the ones discussed by Camargo et al [27] on which the dynamics is synchronized. A figure similar to Fig.…”
Section: Fig 4 Plots Similar Tomentioning
confidence: 52%
See 1 more Smart Citation
“…The mechanism for induced multistability in the case of global coupling can be understood in a similar manner. However, in addition to synchronized attractors appearing due to the fixed points A ∓ , the systems can also exhibit other attractors, A 1,2 , similar to the ones discussed by Camargo et al [27] on which the dynamics is synchronized. A figure similar to Fig.…”
Section: Fig 4 Plots Similar Tomentioning
confidence: 52%
“…Although this is not easily demonstrated for the ensemble of coupled Lorenz oscillators due to the high dimensionality, a study of two coupled Lorenz oscillators gives some indication. For the case of r = 28, Camargo, Viana, and Anteneodo [27] showed that there were two attractors (inand out-of-phase) with intermingled basins of attraction that were riddled for sufficiently large coupling. A more detailed analysis of two coupled Lorenz attractors with r near the Hopf boundary [28] shows that there are several chaotic attractors with complicated basins.…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to mention that Ω 1 ∩ Ω 2 = ∅, meaning that there is no initial condition that results in both attractors. Besides the complex structure and interaction between these basins of attraction, the property of intermingle and riddled basins that have been previously described in both discrete and continuous time systems as refereed in [27,28], cannot be attribute in this case due to their formal definition.The resulting size of each one of the attractors A 1,2 and the Lyapunov exponent remain invariant to the size of S p and Λ, respectively.…”
Section: Multistable Switching System With Symmetric Equilibriamentioning
confidence: 99%
“…Camargo et al considered a system of two identical linearly coupled Lorenz oscillators presenting synchronization of chaotic motion for a specified range of the coupling strength. They verified the existence of global synchronization and antisynchronization attractors with intermingled basins of attraction, such that the basin of one attractor is riddled with holes belonging to the basin of the other attractor and vice versa [17]. Finally, Li et al concerned with model-free control of the Lorenz chaotic system, where only the online input and output are available, while the mathematic model of the system is unknown [18].…”
Section: Introductionmentioning
confidence: 99%